Ear Witness Inventory - Abu Hamdan, Lawrence; Lawrence Abu Hamdan (Vienna; Berlin; Secession; Revolver Publishing, 2020)
Catalog of an exhibition held at the Secession, December 1, 2020-February 7, 2021. In both his art and his audio investigations, Lawrence Abu Hamdan grapples with sound, speech, memory, and the quest for truth in the context of today$1 (Bs legal and humanitarian crises. A central concern that is woven through many of his works, including sound and video installations, objects, and research-based documentaries, is his engagement with questions around the relevance and critique of acoustic clues and the reports of earwitnesses as part of the gathering of evidence in legal proceedings. In his exhibition at the Secession, the artist takes these concerns a step further. He presents altogether four works from two series that probe questions related to the witness testimony. The display takes a stand for other forms of witnessing that break the juridical framework for eye- and earwitnesses$1 (Bstatements and perhaps pose a more general challenge to our notions of law and justice, of truth and how it is established.s
English
Keywords: Contemporary Art; N4390-5098 Exhibitions